The impact of the teacher education study program on the development of TPACK - Karolina Dobi Barišić; Maja Brust Nemet (Revija za Elementarno Izobraževanje, 2023)
This study compares students’ TPACK at the beginning and at the end of their college education according to their involvement and the number of computer science courses. Research was conducted at the Faculty of Education in Osijek, Croatia, with the same generation of students, in 2015 (N=71) and 2020 (N=43). The results showed a statistically significant difference for Technological, Pedagogical and Content Knowledge, for all students in the sample and for students with additional computer science courses. In the case of overall TPACK, there is no difference for the overall sample of students but for students with additional computer science courses, the difference is significant.